2022
DOI: 10.1002/vms3.758
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Listeria monocytogenes isolated from wildlife in central New York

Abstract: Background Listeria monocytogenes (Lm) present in farming soil and food‐processing facilities threatens food safety, but little is known about the carriage of Lm by wildlife. Objectives We estimated the prevalence of faecal Lm shedding among wildlife admitted to a veterinary medical teaching hospital in central New York and characterized a subset of the Lm isolates. Methods Wildlife samples were collected between May 2018 and December 2019. We characterized the Lm isolates by assessing the growth at three temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The presence of an ST6 isolate carrying virulence genes involved in invasion and adherence mechanisms could be relevant in wildlife animals. In fact, they could play an active role as carriers of possibly pathogenetic and virulent strains, and contribute to the distribution of L. monocytogenes in the environment [ 38 , 39 ]. This is even more true when considering species such as Caretta caretta , which can migrate for hundreds or thousands of kilometers [ 6 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an ST6 isolate carrying virulence genes involved in invasion and adherence mechanisms could be relevant in wildlife animals. In fact, they could play an active role as carriers of possibly pathogenetic and virulent strains, and contribute to the distribution of L. monocytogenes in the environment [ 38 , 39 ]. This is even more true when considering species such as Caretta caretta , which can migrate for hundreds or thousands of kilometers [ 6 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…To induce an infection, L. monocytogenes expresses virulence genes organized into groups such as the Internalin gene operon (encoded by inlA to inlK ), listerial pathogenicity islands (encoded by LIPI -1to LIPI-4 ) and stress survival islets (SSIs) [ 4 ]. Accordingly, two recent studies showed that strains belonging to CC388 harbor LIPI-4, but not inLF, inlG, SSI-1 and SSI-2 [ 25 , 26 ]. This pathogenic island is also present in isolates belonging to CC4 that cause cerebral and placental tissue tropism [ 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, L. monocytogenes needs the actA gene, which encodes a protein involved in actin polymerization and motility, to move intracellularly and spread from one cell to another [ 149 ]. In a study performed by Chen [ 150 ] in the USA, the common prevalence of inlA , inlB , and actA genes was noted among L. monocytogenes strains isolated from wild birds; moreover, these strains were identified as putatively hypervirulent L. monocytogenes strains.…”
Section: Virulence Profiles and Genetic Diversity Of Bacteria Isolate...mentioning
confidence: 99%